THE ACCOUNT OF MATERIALS NONLINEARITY IN FINITE ELEMENT ANALYSIS OF REINFORCED CONCRETE COLUMNS OF RECTANGULAR CROSS SECTIONS - V. P. Agapov; A. V. Vasiljev; K. R. Aidemirov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The way of the account of nonlinearity of deformation of concrete and reinforcement bar and cracking in concrete in finite element analysis of reinforced concrete columns of rectangular section is described. The column is made from solid eight nodes elements modelling concrete, and the rod elements modelling reinforcement bar, thus the column is considered as a superelement which characteristics are resulted in the nodes laying at end faces of a column.Diagrams of deformation of concrete and armature are accepted according to working building norms. The superelement developed was implemented into finite element program PRINS, and consisting of this program can be used for physically nonlinear analysis of building structures, containing the reinforced concrete columns of fectangular cross section.